Effect of Disease Severity in Asthma and Chronic Obstructive Pulmonary Disease on Inhaler-Specific Inhalation Profiles Through the ELLIPTA ® Dry Powder Inhaler - Prime, David; de Backer, Wilfried; Hamilton, Melanie; Cahn, Anthony; Preece, Andrew; Kelleher, Dennis; Baines, Amanda; Moore, Alison; Brealey, Noushin; Moynihan, Jackie (Journal of aerosol medicine, 2015)
Two studies were undertaken to characterize the maximal effort inhalation profiles of healthy subjects and patients with asthma or chronic obstructive pulmonary disease (COPD) through a moderate-resistance dry powder inhaler (DPI). Correlations between inhaler-specific inhalation characteristics and inhaler-independent lung function parameters were investigated. Healthy subjects (n = 15), patients with mild, moderate, or severe asthma (n = 45), and patients with mild, moderate, severe, or very-severe COPD (n = 60) were included in the studies. Inhalation pressure drop versus time profiles were recorded using an instrumented ELLIPTA® DPI or bespoke resistor component with equivalent resistivity. Inhaler-independent lung function assessments included pharyngometry, spirometry, plethysmography, and diffusion. For the inhaler-specific inhalation profiles, the mean maximal effort peak inspiratory flow rates (PIFRs) varied across the subgroups from 65.8-110.6 L/min (range: 41.6-142.9). Peak pressure drop, PIFR, inhaled volume, and average inhalation flow rate (primary endpoints) did not differ markedly between healthy subjects and patients with asthma or mild COPD. Moderate, severe, and very-severe COPD patients demonstrated lower mean peak pressure drops, PIFRs and inhaled volumes, which tended to decrease with increasing COPD severity. Severe and very-severe COPD patients demonstrated shorter mean inhalation times compared with all other participants. Inhaler-independent lung function parameters were consistent with disease severity, and statistically significant (p < 0.05) strong correlations (R > 0.7) with components of the inhaler-specific inhalation profiles were observed in the COPD cohort; correlations in the asthma cohort tended to be weaker. All participants achieved a maximal effort PIFR ≥ 41.6 L/min through the moderate resistance of the ELLIPTA inhaler. Patients with asthma achieved similar inhalation profiles to healthy subjects, but increasing COPD severity tended to reduce a patient's inhalation capability. Correlation analyses suggest that some lung function parameters may be a useful indicator of ability to inhale efficiently through a moderate-resistance DPI, such as the ELLIPTA inhaler.